2023
DOI: 10.1681/asn.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Molecule TIGIT Regulates Kidney T Cell Functions and Contributes to AKI

Abstract: Significance Statement T cells mediate pathogenic and reparative processes during AKI, but the exact mechanisms regulating kidney T cell functions are unclear. This study identified upregulation of the novel immune checkpoint molecule, TIGIT, on mouse and human kidney T cells after AKI. TIGIT-expressing kidney T cells produced proinflammatory cytokines and had effector (EM) and central memory (CM) phenotypes. TIGIT-deficient mice had protection from both ischemic and nephrotoxic AKI. Single-cell RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In essence, TIGIT expression was induced upon stimulated with anti-CD3 and anti-CD28 in vitro and reached a peak at 24 hour and then decreased over time ( 18 ). Previous studies also showed that TIGIT-expressing T cells possessed a functionally proinflammatory profile and memory phenotype in context of experimental acute kidney injury, donor-specific hyperresponsiveness (DSH) and systemic lupus erythematosus (SLE) ( 39 41 ). TIGIT + CD8 + T cells were suggested to maintain an intrinsic capacity to kill targets in HIV-infected individuals instead of exhibiting an exhausted function ( 42 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In essence, TIGIT expression was induced upon stimulated with anti-CD3 and anti-CD28 in vitro and reached a peak at 24 hour and then decreased over time ( 18 ). Previous studies also showed that TIGIT-expressing T cells possessed a functionally proinflammatory profile and memory phenotype in context of experimental acute kidney injury, donor-specific hyperresponsiveness (DSH) and systemic lupus erythematosus (SLE) ( 39 41 ). TIGIT + CD8 + T cells were suggested to maintain an intrinsic capacity to kill targets in HIV-infected individuals instead of exhibiting an exhausted function ( 42 ).…”
Section: Discussionmentioning
confidence: 98%
“…Although TIGIT deficiency or TIGIT blockade led to increased T cell proliferation, robust cytokine production and degranulation ( 39 , 43 , 44 ), murine models of different disease backgrounds showed various responses to the loss of TIGIT signaling pathway. Blocking TIGIT by antibody or genetic knockout enhanced NK cell activation and aggravated liver injury in a poly I:C/D-GalN-induced model of acute hepatitis ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes mediate pathogenic and reparative processes during AKI, while the exact mechanisms regulating kidney T cell functions remain elusive [ 37 ]. Gong et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the current issue of JASN, Béland et al provide an intriguing new insight into this area by demonstrating that HLA-DQ, DR, and DP proteins follow distinctly different expression dynamics on endothelial cells under inflammatory conditions. 9 Using human endothelial colony forming cell (ECFC)-derived cell lines, the authors observed that there was lower surface expression and greater interindividual variability of expression of HLA-DQ compared with HLA-DR and HLA-DP proteins after stimulation with IFNg. In pursuing this further, they assessed the relationship between HLA-DQ genotype and protein expression across their panel of ECFC-derived lines.…”
Section: Author Contributionsmentioning
confidence: 99%
“…In this issue of JASN , Noel et al describe how TIGIT may mediate kidney T-cell contributions to AKI, providing evidence which supports its potential as a therapeutic target in human AKI. 9 To investigate the role of TIGIT in AKI, mice were subjected to either ischemia-reperfusion (IR) injury or cisplatin injection and human samples were obtained from patients undergoing nephrectomy both before and after renal pedicle clamping. The authors observed increased TIGIT expression in kidney CD4, CD8, and double-negative (DN) T-cell populations after murine IR injury and the percentage of human CD8+ and DN T cells that were TIGIT+ increased after renal pedicle clamping in human samples.…”
mentioning
confidence: 99%